Analisis Efektifitas Jalur Khusus Sepeda di Jalan A. P. Pettarani Kota Makassar - Zaputra, Andi Qalfi; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2024)
In Makassar City, transportation plays an important role in improving population mobility. This increase in mobility in Makassar City has resulted in the use of private vehicles for transportation, which has a number of disadvantages. Bicycle facilities, on the other hand, remain ineffective due to bicycle lanes deemed unsafe from motorized vehicles, poor pavement, and a lack of bicycle signage. The issue raised is also a research topic, namely, how effective is the implementation of bicycle lanes in the Makassar City area? The collection of data on Jalan A. P. Pettarani is one of the study's limitations. Effectiveness is calculated using the BLOS (Bicycle Level of Service) methodology. The BLOS value of 2.94 on Jalan A. P. Pettarani was in the range of 2.5–3.5, rated C, showing that the route was less effective for bicycles. When traffic volume is low or road conditions are described as quiet, add protection for bicycle lanes with speed bumps (Type-A Bicycle Lane) to increase the BLOS value..